Penerapan Literasi Sains Dalam Pembelajaran Fisika Di Era Society 5.0 - Lestari, Ika; B.K Gultom, Onggung; Saputri Zebua, Fransiska (Jurusan Teknik Sipil, Politeknik Negeri Ketapang, 2022)
In the era of society 5.0, literacy is one of the needs for every human being to fulfill the needs of a human-centered life that collaborates with technology. One of the important literacy in this era is scientific literacy. The application of scientific literacy can be done through learning physics. This study aims to examine the application of scientific literacy in physics learning so that it is useful in improving the quality of world competition in education in the era of society 5.0. The method used in this research is literature study. The data collection technique in this research is to collect information and data from various library materials such as books, articles, previous research, notes and journals related to the application of scientific literacy in physics learning in the era of society 5.0. Physics learning can be used as a process, product, attitude and technology. Physics learning that can achieve scientific literacy is learning that is in accordance with the nature of physics learning. One of the skills needed in the era of society 5.0 is scientific literacy skills. Between the era of society 5.0 and scientific literacy have the same goal in responding to all challenges of social life and improving decision-making skills